Yorkshire terrier : tiny but tough - Fetty, Margaret (New York : Bearport Pub., 2009)
Provides an introduction to the Yorkshire terrier that discusses the breed's history, physical characteristics, and behaviors and looks at Yorkies in popular culture.
Includes bibliographical references (p. 31) and index.
4.9
3-6
Keywords: Yorkshire terrier -- Juvenile literature; Dogs; Yorkshire terrier; Dogs; Yorkshire terriers